2020
DOI: 10.1126/science.abb6320
|View full text |Cite
|
Sign up to set email alerts
|

Denisovan DNA in Late Pleistocene sediments from Baishiya Karst Cave on the Tibetan Plateau

Abstract: A late Middle Pleistocene mandible from Baishiya Karst Cave (BKC) on the Tibetan Plateau has been inferred to be from a Denisovan, an Asian hominin related to Neanderthals, on the basis of an amino acid substitution in its collagen. Here we describe the stratigraphy, chronology, and mitochondrial DNA extracted from the sediments in BKC. We recover Denisovan mitochondrial DNA from sediments deposited ~100 thousand and ~60 thousand years ago (ka) and possibly as recently as ~45 ka. The long-term occupation of BK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(87 citation statements)
references
References 113 publications
0
82
0
5
Order By: Relevance
“…Beyond reconstructing the occupational history of Denisova Cave, our results have wider implications for understanding the human past. First, fragments of Denisovan mtDNA recovered from the middle Middle Palaeolithic layers deposited in Denisova Cave after 80 ka consistently show the highest similarity to the mtDNA of Denisova 3 and Denisova 4, as do mtDNA fragments retrieved from sediments at Baishiya Karst Cave on the northeastern flank of the Tibetan Plateau that are broadly contemporaneous in age (70-45 ka) 27 . This pattern suggests that this lineage was the most abundant mtDNA type carried by Denisovans after 80 ka.…”
Section: Discussionmentioning
confidence: 93%
“…Beyond reconstructing the occupational history of Denisova Cave, our results have wider implications for understanding the human past. First, fragments of Denisovan mtDNA recovered from the middle Middle Palaeolithic layers deposited in Denisova Cave after 80 ka consistently show the highest similarity to the mtDNA of Denisova 3 and Denisova 4, as do mtDNA fragments retrieved from sediments at Baishiya Karst Cave on the northeastern flank of the Tibetan Plateau that are broadly contemporaneous in age (70-45 ka) 27 . This pattern suggests that this lineage was the most abundant mtDNA type carried by Denisovans after 80 ka.…”
Section: Discussionmentioning
confidence: 93%
“…Currently, existing archaeological evidence generally supports two settlement scenarios. The archaeological sites from middle to late Holocene ( 62 65 ) indicate that year-round large-scale settlements of people on the plateau started after 3.6 ka facilitated by the advent of agriculture, while analyses on the mobility of hunter-gatherers ( 66 – 68 ) suggest that permanent inhabitation (most likely on a smaller scale) may have occurred more distantly in the past. Our estimate of the Denisovan East Asian-specific admixture time (48 ka) from tract lengths surrounding the EPAS1 gene is larger than most estimates of when modern humans permanently settled in the Tibetan Plateau, suggesting that the admixture most likely occurred outside of this region.…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of genome-wide data from multiple animal species from a single Pleistocene soil sample opens a new avenue compared to what has previously been learned from sediment DNA (Ardelean et al, 2020; Slon et al, 2017; Willerslev et al, 2003; Zhang et al, 2020). Using this data we were able to make inferences about the genetic ancestry and history of three past mammalian populations that lived in the Southern Caucasus ∼25 ka.…”
Section: Discussionmentioning
confidence: 99%
“…A ground-breaking study showed DNA preservation in clay-rich sediments for at least 240 ky. (Slon et al, 2017), and used targeted enrichment to recover sufficient numbers of fragments to reconstruct mtDNA phylogenies of Neanderthals and Denisovans. A recent study similarly recovered Denisovan mitochondrial DNA from sediments deposited ∼100 kya and ∼60 kya from Baishiya Karst Cave (BKC) on the Tibetan Plateau (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 98%